The Effects of Work-Life Benefits on Employment Outcomes in Canada: A Multivariate Analysis - Fang, Tony; Lee, Byron; Timming, Andrew; Fan, Di (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2019)
The aim of this study is to examine the empirical question of how the provision of work-life benefits is associated with wages, promotions, and job satisfaction. This is an important question for industrial relations scholars and one that, as yet, has no definitive answer.In order to answer this question, we employ both economic theory and methods. Specifically, the economic theories being tested are the compensating wage differentials theory and the efficiency wage theory. To test the efficacy of each theory, we use econometric techniques using longitudinal data from the most recent Workplace and Employee Survey of Canada. We use regression to unpack the effects of work-life benefits on various employment outcomes and employ instrumental variables to mitigate against reverse causality.We find broad support for the efficiency wage theory. Alternatively stated, we find that increases in benefits are not associated with decreases in wages and other employment outcomes. If bundled correctly, work-life benefits are positively associated with increased wages, a greater number of promotions, enhanced employee morale in the form of job satisfaction, and improved employee retention.These results suggest that the provision of work-life benefits is not a zero-sum game for employers and employees. On the contrary, it appears that both parties to the employment relationship can benefit from work-life benefits.